MENGEMBANGKAN DISIPLIN ANAK USIA DINI MELALUI METODE PEMBIASAAN BERBASIS HINDU DI TK DHARMA KUMARA IV BUDUK - Ayu Nikiani Ni Komang; Aria Prima Dewi PF Kadek; Luwih I Made (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Developing Hindu-based Early Childhood Discipline can be done by using the habituation method. Through habituation activities, the child will get used to discipline. The discipline of children is taught about behaving in ways that are consistent with the standards of their social groups. With the inculcation of discipline from an early age, especially based on Hinduism, will certainly have a great influence on the child, a child will become accustomed to and consider that it must be done. The issues to be discussed include (1) application in developing Early Childhood discipline through Hindu-based habituation methods in TK Dharma Kumara IV Buduk (2) obstacles encountered in developing Early Childhood discipline through Hindu-based habituation methods in TK Dharma Kumara IV Buduk (3) supporting factors in developing Early Childhood discipline through Hindu-based habituation methods at Kindergarten Dharma Kumara IV Buduk. This study aims to (1) Know how to apply in developing the discipline of Early Childhood through Hindu-based habituation methods in Kindergarten Dharma Kumara IV Buduk (2) find out the obstacles faced in developing Early Childhood discipline through Hindu-based habituation methods in Kindergarten Dharma Kumara IV Buduk (3) knows the supporting factors in developing Early Childhood discipline through Hindu-based habituation methods at TK Dharma Kumara IV Buduk.